HUBUNGAN TINGKAT LITERASI KESEHATAN MENTAL DENGAN KECEMASAN SISWA DI SMA PSKD II JAKARTA - Ides, Stefanus Andang; Rirendri, Ittai Hosan (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2025)
Anxiety is a major factor influencing adolescents' mental health. During adolescence, mental health literacy is crucial for understanding, seeking information, and recognizing signs of mental disorders, enabling appropriate actions. This study aims to analyze the relationship between mental health literacy levels and anxiety among students at SMA PSKD II Jakarta. Employing a cross-sectional quantitative design, the study's population comprised 157 students from grades 10 to 12, with a sample of 68 respondents determined using Slovin's formula. Data were collected via questionnaires. Results indicated that students with good mental health literacy levels exhibited moderate anxiety (54.4%), while those with sufficient literacy levels also showed moderate anxiety (1.5%). Spearman's rho test revealed a significant relationship between mental health literacy levels and anxiety among students at SMA PSKD II Jakarta (p = 0.047). This research is expected to serve as a reference for students, educators, institutions, and future researchers to explore mental health issues further.